SEKOLAH SEHAT GENERASI EMAS NOL STUNTING MULAI DARI SEKOLAH DASAR - Ahmad Antoni; Anna Maria Oktaviani; Muhammad Fathul Hidayatullah (STKIP Subang, 2026)
Stunting is a chronic nutritional problem that remains a serious challenge in Indonesia and significantly affects the long-term quality of human resources. Numerous studies indicate that stunting influences physical growth, cognitive development, academic achievement, and productivity in adulthood. Stunting prevention requires comprehensive, integrated, and sustainable efforts involving multiple sectors, including education. Elementary schools play a strategic role in shaping healthy behaviors, nutritional knowledge, and positive lifestyle habits from an early age through the implementation of healthy school programs. This article aims to examine the role of healthy schools in supporting the realization of a stunting-free golden generation starting from elementary education. The method employed is a literature review analyzing national and international journal articles, reports from global health organizations, and government policies related to stunting and school health. The findings indicate that the implementation of healthy school programs including nutrition education, clean and healthy lifestyle practices, regular physical activity, provision of healthy school environments, and collaboration among schools, families, and communities contributes significantly to stunting prevention. Therefore, healthy schools serve as a key foundation for developing a healthy, intelligent, and competitive future generation. In addition, the healthy school approach strengthens intersectoral collaboration between education, health services, and families in addressing nutritional problems among school-age children. Through systematic health promotion, routine monitoring, and the integration of nutrition education into learning activities, schools can function as early prevention settings that reinforce the outcomes of interventions implemented during the first 1,000 days of life